Early Hyperglycemia in Pediatric Traumatic Brain Injury Predicts for Mortality, Prolonged Duration of Mechanical Ventilation, and Intensive Care Stay - Shu-Ling Chong; Sumitro Harjanto; Daniela Testoni; Zhi Min Ng; Chyi Yeu David Low; Khai Pin Lee; Jan Hau Lee (International Journal of Endocrinology)
We aim to study the association between hyperglycemia and in-hospital outcomes among children with moderate and severe traumatic brain injury (TBI). This retrospective cohort study was conducted in a tertiary pediatric hospital between 2003 and 2013. All patients < 16 years old who presented to the Emergency Department within 24 hours of head injury with a Glasgow Coma Scale (GCS) ≤ 13 were included. Our outcomes of interest were death, 14 ventilation-free, 14 pediatric intensive care unit- (PICU-) free, and 28 hospital-free days. Hyperglycemia was defined as glucose > 200 mg/dL (11.1 mmol/L). Among the 44 patients analyzed, the median age was 8.6 years (interquartile range (IQR) 5.0–11.0). Median GCS and pediatric trauma scores were 7 (IQR 4–10) and 4 (IQR 3–6), respectively. Initial hyperglycemia was associated with death (37% in the hyperglycemia group versus 8% in the normoglycemia group, p=0.019), reduced median PICU-free days (6 days versus 11 days, p=0.006), and reduced median ventilation-free days (8 days versus 12 days, p=0.008). This association was however not significant in the stratified analysis of patients with GCS ≤ 8. Conclusion. Our findings demonstrate that early hyperglycemia is associated with increased mortality, prolonged duration of mechanical ventilation, and PICU stay in children with TBI.